Mania Induced by Epidural Steroid Injection in an Elderly Female With No Psychiatric History - Chen, Pauline (Cureus, 2021)
The psychiatric risks of epidural steroid injections for chronic pain in a geriatric patient with no prior psychiatric history are presented here. A 76-year old Caucasian female presented to the emergency department with her family for an inability to sleep, confusion, and behavioral outbursts. The mood instability and psychosis were reported as having started a week after her third epidural steroid injection for low-back pain associated with a prior fall. After 12 days of mixed treatment outcomes and increasing paranoia without any localized neurological findings, the patient was transferred to the geriatric psychiatry unit. Upon admission to the inpatient unit, she was loud, grandiose, verbally aggressive, unable to sleep, hyper-religious, paranoid, and identified her husband and daughter as demons. The patient was started on risperidone and valproic acid for the management of psychosis and manic symptoms. Hyper-religiosity and paranoia greatly improved within a week, though the patient remained very talkative and tangential, with a disorganized thought process. Valproic acid was titrated to 500 mg twice a day, yielding a level of 56.2 ug/ml, accompanied by improvement to mild talkativeness and circumstantiality. She was able to interact appropriately, with minimal lorazepam requirement, and discharged with a linear thought process and absence of psychosis. On outpatient follow up, there were minimal residual mania and no recurrence of psychosis, allowing her to be weaned off valproic acid and to discontinue risperidone. Two months later, symptoms resolved completely. The persistence of this patient’s psychosis for nearly one month, and mania for about three months, underscores the importance of careful risk-benefit analysis before initiating epidural steroids. This is particularly important in elderly patients who may be more susceptible to psychiatric adverse effects that can outlast any analgesic benefits.